THE TRADITION OF TEACHER-STUDENT, SCHOOL-MADRASA IN "HAYRAT UL-ABROR" - Aziza Dilmurod qizi Uralova; Buronova Ra'no Abdujabborovna; Toshqobilov Umid Sharofiddinovich (Scholar Express Journal, 2022)
Navoi has successfully continued the tradition of teacher-student, schoolmadrasa in such a way that the world has witnessed it. The difference between Navoi's "hamsa" was that it was written in Turkish, not Persian. The immortal truth of the centuries, which shows that this tradition has been beautifully fulfilled, is that, despite the passage of so many epochs, these works are still recognized by the people, they are not obsolete, but still alive, re-read it is evident in its ability to arouse pleasure again. The value of the works increased, but did not decrease
Keywords: Fasohat; Afsar; Guhar; Anbarsirisht